PENERAPAN METODE UTAUT PADA MINAT DAN PERILAKU PENGGUNAAN MOBILE BANKING DI KABUPATEN KEBUMEN - Kusumaningrum, Dita; Mahardika, Arya Samudra (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
This study aims to analyze the factors that influence the interest and behavior of mobile banking in the people of Kebumen Regency using the UTAUT model approach. The sampling technique in this study was to use purposive sampling. Respondents in this study were 104 banking customers who had used mobile banking in Kebumen Regency. This research was tested using SEM-PLS with WarpPLS 8.0. The results in this study indicate that effort expectations, social influence and behavioral intention have a positive effect on use behavior. While performance expectations and facility conditions have no effect on use behavior.